2012
DOI: 10.1245/s10434-012-2652-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Better Nodal Staging System for Melanoma: The Clinical Relevance of Metastatic Disease Confined to the Sentinel Lymph Nodes

Abstract: When metastatic melanoma overwhelms the SLN and involves NSLNs, the biologic behavior changes to portend a worse survival, regardless of the total node count positive. These data make the argument that the current N staging system should be changed to incorporate SLN vs NSLN involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 13 publications
4
25
0
Order By: Relevance
“…In the literature, it has been reported that NM has a higher median thickness ranging from 2.3 to 3.2 mm at time of diagnosis compared to SSM ranging from 0.88 to 1.1 mm, which leads to a higher likelihood of having a metastatic disease at the time of diagnosis. The median Breslow thickness for metastatic melanomas ranges more frequently between 1 and 4 mm and this is comparable with the range we found (mean 3.05 mm, median 2.1 mm). In the literature NM with a higher Breslow thickness is more likely to be found in metastatic melanoma patients as this tumour type tends to have higher tumour thickness .…”
Section: Discussionsupporting
confidence: 90%
“…In the literature, it has been reported that NM has a higher median thickness ranging from 2.3 to 3.2 mm at time of diagnosis compared to SSM ranging from 0.88 to 1.1 mm, which leads to a higher likelihood of having a metastatic disease at the time of diagnosis. The median Breslow thickness for metastatic melanomas ranges more frequently between 1 and 4 mm and this is comparable with the range we found (mean 3.05 mm, median 2.1 mm). In the literature NM with a higher Breslow thickness is more likely to be found in metastatic melanoma patients as this tumour type tends to have higher tumour thickness .…”
Section: Discussionsupporting
confidence: 90%
“…Although this finding is somewhat counterintuitive, it echoes retrospective data from multiple institutions. 13,14 This confirmation in a prospective trial of the large effect of nonsentinel node status on prognosis reaffirms its staging value. A lack of this information may impede the most appropriate risk stratification and selection of adjuvant therapy for patients who do not undergo completion lymph-node dissection.…”
Section: Discussionmentioning
confidence: 66%
“…Since most such patients have all nodal metastases removed by means of the sentinel-node biopsy procedure, they cannot derive additional therapeutic value from completion lymph-node dissection. Even microscopic nonsentinel-node metastases portend a markedly worse prognosis, similar to that of patients with bulky, clinically diagnosed metastases, 13,14 than the prognosis in patients with metastases that are limited to the sentinel lymph nodes. Patients with nonsentinel-node metastasis may be unlikely to benefit from early dissection.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although there are several arguments against performing a CLND in patients with minimal melanoma disease burden in the SLN, such as morbidity of lymphadenectomy and emerging targeted immunotherapies, there is value of a CLND with respect to staging and prognosis . Multiple studies have reported that the presence of metastatic non‐SLNs is an independent negative prognostic factor associated with significantly lower disease‐free survival, melanoma‐specific survival, and overall survival . Knowing the status of the non‐sentinel nodes is often important for entry into clinical trials .…”
Section: Discussionmentioning
confidence: 99%